Timed restricted feeding cycles drive daily rhythms in female rats maintained in constant light but only partially restore the estrous cycle - Guerrero-Vargas, Natalí N.; Espitia-Bautista, Estefania; Escalona, Rene; Lugo-Martínez, Haydée; Gutiérrez-Pérez, Mariana; Navarro-Espíndola, Raful; Setién, María Fernanda; Boy-Waxman, Sebastián; Retana-Flores, Elizabeth Angélica; Ortega, Berenice; Buijs, Ruud M.; Escobar, Carolina (Frontiers in Nutrition, 2022)
Light at night is an emergent problem for modern society. Rodents exposed to light at night develop a loss of circadian rhythms, which leads to increased adiposity, altered immune response, and increased growth of tumors. In female rats, constant light (LL) eliminates the estrous cycle leading to a state of persistent estrus. The suprachiasmatic nucleus (SCN) drives circadian rhythms, and it interacts with the neuroendocrine network necessary for reproductive function. Timed restricted feeding (RF) exerts a powerful entraining influence on the circadian system, and it can influence the SCN activity and can restore rhythmicity or accelerate re-entrainment in experimental conditions of shift work or jet lag. The present study explored RF in female rats exposed to LL, with the hypothesis that this cyclic condition can rescue or prevent the loss of daily rhythms and benefit the expression of the estrous cycle. Two different feeding schedules were explored: 1. A 12-h food/12-h fasting schedule applied to arrhythmic rats after 3 weeks in LL, visualized as a rescue strategy (LL + RFR, 3 weeks), or applied simultaneously with the first day of LL as a preventive strategy (LL + RFP, 6 weeks). 2. A 12-h window of food intake with food given in four distributed pulses (every 3 h), applied after 3 weeks in LL, as a rescue strategy (LL + PR, 3 weeks) or applied simultaneously with the first day of LL as a preventive strategy (LL + PP, 6 weeks). Here, we present evidence that scheduled feeding can drive daily rhythms of activity and temperature in rats exposed to LL. However, the protocol of distributed feeding pulses was more efficient to restore the day–night activity and core temperature as well as the c-Fos day–night change in the SCN. Likewise, the distributed feeding partially restored the estrous cycle and the ovary morphology under LL condition. Data here provided indicate that the 12-h feeding/12-h fasting window determines the rest-activity cycle and can benefit directly the circadian and reproductive function. Moreover, this effect is stronger when food is distributed along the 12 h of subjective night.